A Functional Study of Lithics from Vænget Nord, a Mesolithic Site at Vedbæk, N.E. Sjælland - Juel, Helle; Brinch, Erik (Journal of Danish Archaeology, 1985)
A Functional Study of Lithics from Vænget Nord, a Mesolithic Site at Vedbæk, N.E. Sjælland